Vilka är de långvariga effekterna av NGOs arbete inom utbildning i utvecklingsländerna? En fallstudie med fokus på Kenya och Bangladesh - Roble,Madina; Maayouf,Manar (2025)
This study looks at how non-governmental organizations (NGOs) help improve education in Kenya and Bangladesh, as well as the challenges they face. It focuses on two examples: Room to Read in Kenya and Barnmissionen in Bangladesh. The study explores how NGOs use different strategies to fill gaps in education where the government cannot meet all needs. Neo-institutionalism is used to understand how global trends, local customs, and institutional systems affect their work. The findings show that Room to Read focuses on improving literacy and supporting girls' education in Kenya, while Barnmissionen works to provide basic education for marginalized groups in Bangladesh. Both organizations face challenges such as relying on external funding, dealing with cultural norms, and working within bureaucratic systems. Kenya offers more flexibility for NGOs because of its decentralized education system and better cooperation between the government and NGOs. In contrast, Bangladesh has stricter bureaucratic systems, which make it harder for NGOs to expand their work or introduce new ideas. The study concludes that long-term improvements in education need stronger cooperation between NGOs, governments, and international donors. To succeed, NGOs must create strategies that combine global standards with local needs, ensuring better access to quality education for all children.
Keywords: NGO; Kenya; Bangladesh; Neo-institutionalism; education